THE FACTORS INFLUENCE ON THE INTERVENTION OF CARBOHYDRATE MOUTH RINSE IMPROVING ENDURANCE PERFORMANCE: A SYSTEMATIC REVIEW - Nadia Md Noor; Al Hafiz Abu Bakar; Harris Kamal Kamaruddin; Ahmad Dzulkarnain Ismail; Ellail Ain Mohd Aznan (Journal of Islamic, Social, Economics and Development, 2023)
The ergogenic effects of carbohydrate (CHO) mouth rinse on exercise performance have been well-documented. A unique energy signalling pathway that can increase exercise effectiveness by stimulating different brain areas linked to reward, motivational, and motor control behaviour has been extensively cited as the mechanism underpinning CHO mouth rinse. There is, however, a paucity of research carefully reviewing the variables that affect the effectiveness of CHO mouth rinse. Therefore, the purpose of the study is to provide systematically review on the factors influence CHO mouth rinse on endurance performance. A systematic review was carried out by using online database (Google scholar and Scopus), as well as perhaps a conference proceeding related papers, were reviewed. Thirty-three related studies with CHO mouth rinse have been screened, however only 28 studies that eligibility accepted for reviewed in qualitative synthesis. The findings observed three main factors which criteria of athlete, intervention and concentration that influenced CHO mouth rinse during endurance exercise performance. Base from the review, the suitable criteria of participant that can be used as intervention experiment were elite and trained athlete. When considering the exercise routine, both cycling and running can be employed as an intervention for CHO mouth rinse as long as the speed and wattage modification are automated. While 6-6.4% of concentration in CHO shown a good enough to enhance exercise performance. Analyses all three factors that been reviewed can improved and provide a better idea for future experimental study of CHO mouth rinse.